Evaluasi Implementasi dan Strategi Pengembangan Teaching Factory pada Sekolah Menengah Kejuruan (SMK) di Kabupaten Kebumen Jawa Tengah - Mulyanto Mulyanto (LP2M Universitas Sarjanawiyata Tamansiswa, 2020)
This research is an evaluative type of CIPPO model research. CIPP (Context, Input, process, and Product) developed by Stufflebeam plus O (Outcome). The sampling technique was purposive sampling which was done by interview and documentation. The targets of this study were the principal, Head of the Engineering and Light Vehicle Engineering Program, Head of Teaching factory Production Unit, and several students involved in teaching factory activities. The results of the study showed that: 1) The effectiveness of teaching factory implementation at SMK Muhammadiah Kutowinangun was very good while in SMKN 2 is quite good. 2) Supporting factors for the implementation of teaching factory in the two SMKs studied are relatively the same, namely support from all stakeholders, adequate facilities and infrastructure, competent teachers. 3) The inhibiting factor of teaching factory implementation in the two schools studied among others is the absence of marketing staff (promotion and order seekers), the absence of technicians who specifically serve customers. 4) The strategy used in the development of teaching factories in the two SMKs studied was to use the 4 P marketing strategy, namely Product, Place, Price, and Promotion (Times New Roman 11, spasi tunggal, dan cetak miring).